Positive electrode active material for lithium secondary battery, its manufacturing method, positive electrode and lithium secondary battery including the same

By forming nickel-based lithium transition metal oxide active materials with giant primary particles and a lithium-metal oxide coating, the structural issues of conventional nickel-based materials are addressed, resulting in improved thermal stability and output performance with reduced resistance and impurities.

JP7602042B2Active Publication Date: 2024-12-17LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023536543
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-24
Filing Date
2021-12-15
Publication Date
2024-12-17
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

Conventional nickel-based lithium transition metal oxides, particularly those with high nickel content, suffer from structural issues leading to poor chemical and thermal stability, increased resistance, and reduced output performance due to the agglomeration of fine primary particles into secondary particles, which also lead to gas generation and decreased lifespan.

Method used

The development of nickel-based lithium transition metal oxide positive electrode active materials with a secondary particle morphology formed by agglomerating giant primary particles, coated with a lithium-metal oxide layer, which are produced without a water washing step to minimize lithium impurities and reduce surface damage, thereby improving thermal stability and output characteristics.

Benefits of technology

The proposed solution results in a positive electrode active material with lower resistance during charging and discharging, enhanced output characteristics, and improved thermal stability by minimizing the interface between secondary particles and reducing lithium impurities to 0.25% by weight or less.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602042000002
    Figure 0007602042000002
  • Figure 0007602042000001
    Figure 0007602042000001
Patent Text Reader

Abstract

The present invention relates to a lithium-metal oxide coating layer formed on the surface of a secondary particle having an average particle diameter (D50) of 1 to 10 μm, the secondary particle being formed by agglomerating two or more giant primary particles having an average particle diameter (D50) of 0.5 to 3 μm. a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0≦a≦1.5, 0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for lithium secondary batteries containing large primary particles of a high-nickel (high-Ni) lithium transition metal oxide, and a method for producing the same.

[0002] This application claims priority to Korean Patent Application No. 10-2020-0183835, filed on December 24, 2020, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] In recent years, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have relatively high capacity has been rapidly increasing. In particular, lithium secondary batteries are lightweight and have high energy density, and are in the spotlight as a driving power source for portable devices. Therefore, research and development to improve the performance of lithium secondary batteries has been actively conducted.

[0004] A lithium secondary battery generates electrical energy by oxidation and reduction reactions occurring when lithium ions are inserted / deintercalated at the positive and negative electrodes, with an organic or polymer electrolyte filled between the positive and negative electrodes, which are made of active materials capable of intercalating and deintercalating lithium ions.

[0005] Lithium cobalt oxide (LiCoO2), nickel-based lithium transition metal oxides, lithium manganese oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4), etc. are used as positive electrode active materials for lithium secondary batteries. Among them, lithium cobalt oxide (LiCoO2) is widely used due to its advantages of high operating voltage and excellent capacity characteristics, and is applied as a positive electrode active material for high voltage. However, due to the rising price of cobalt (Co) and unstable supply, there are limitations to its large-scale use as a power source in fields such as electric vehicles, and there is a demand for the development of alternative positive electrode active materials.

[0006] Therefore, nickel-based lithium transition metal oxides, in which part of the cobalt (Co) is replaced with nickel (Ni) or the like, have been developed, as typified by nickel-cobalt-manganese-based lithium transition metal oxides (hereinafter simply referred to as "NCM-based lithium transition metal oxides").

[0007] Meanwhile, the previously developed nickel-based lithium transition metal oxide is in the form of secondary particles formed by agglomeration of fine primary particles having a fine average particle size (D50), and has a large specific surface area and low particle strength. Therefore, when an electrode is manufactured using a positive electrode active material containing secondary particles formed by agglomeration of fine primary particles and then rolled, there is a risk of significant particle cracking, which may result in a large amount of gas generation during cell operation and reduced stability. In particular, in the case of high-content nickel-based (high-Ni) lithium transition metal oxides in which the nickel (Ni) content is increased to ensure high capacity, the chemical stability is further reduced and it is difficult to ensure thermal stability due to the above-mentioned structural problems.

[0008] In an attempt to improve upon the drawbacks of the conventional nickel-based lithium transition metal oxide having a secondary particle form in which fine primary particles are aggregated, a nickel-based lithium transition metal oxide positive electrode active material having a secondary particle form in which large primary particles having a large average particle size (D50) are aggregated has been proposed.

[0009] The nickel-based lithium transition metal oxide positive electrode active material, which is in the form of secondary particles formed by agglomeration of large primary particles, minimizes the interface between the secondary particles, improving problems such as thermal stability, deterioration of life due to side reactions during electrochemical reactions, and gas generation.

[0010] Meanwhile, high-nickel (high-Ni) lithium transition metal oxide positive active materials are usually washed with water to reduce the amount of lithium impurities remaining on the surface. This washing process is advantageous in reducing gas generation by removing lithium by-products on the surface, but is disadvantageous in terms of lifespan due to surface damage to the positive active material particles. In particular, nickel-based lithium transition metal oxide positive active materials in the form of secondary particles formed by the aggregation of large primary particles inherently have a problem of poor output performance, and after the washing process, the output is further deteriorated and the resistance also increases as charging and discharging proceeds. Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide a nickel-based lithium transition metal oxide positive electrode active material having a secondary particle morphology in which large primary particles are aggregated, and thus having low resistance during charging and discharging and improved output characteristics.

[0012] Another object of the present invention is to provide a method for producing a nickel-based lithium transition metal oxide positive electrode active material having a secondary particle morphology in which large primary particles are aggregated, and thus having low resistance during charging and discharging and improved output characteristics.

[0013] An object of still another embodiment of the present invention is to provide a positive electrode and a lithium secondary battery including a nickel-based lithium transition metal oxide positive electrode active material having the above-described characteristics. [Means for solving the problem]

[0014] An aspect of the present invention provides a positive electrode active material for a lithium secondary battery according to the following embodiment.

[0015] The first embodiment is secondary particles with an average particle size (D50) of 1 to 10 μm formed by aggregating two or more giant primary particles with an average particle size (D50) of 0.5 to 3 μm, and a coating layer of lithium-metal oxide formed on the surface of the secondary particles, and includes the giant primary particles are Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and is represented by the metal of the lithium-metal oxide is one or more metals selected from the group consisting of manganese, nickel, vanadium, and cobalt, relates to a positive electrode active material for a lithium secondary battery with a lithium impurity content of 0.25 wt% or less.

[0016] The second embodiment is, in the first embodiment, relates to a positive electrode active material for a lithium secondary battery in which the metal of the lithium-metal oxide is one or more selected from the group consisting of manganese and cobalt.

[0017] The third embodiment is, in the first or second embodiment, relates to a positive electrode active material for a lithium secondary battery in which the average particle size (D50) of the giant primary particles is 0.5 to 2 μm, more specifically 0.8 to 1.5 μm.

[0018] The fourth embodiment is, in any one of the first to third embodiments, relates to a positive electrode active material for a lithium secondary battery in which the average particle size (D50) of the secondary particles is 2 to 8 μm, more specifically 3 to 6 μm.

[0019] The fifth embodiment is, in any one of the first to fourth embodiments, Relates to a positive electrode active material for a lithium secondary battery in which the average crystal size of the giant primary particles is 200 nm or more.

[0020] The sixth embodiment is in any one of the first to fifth embodiments, Relates to a positive electrode active material for a lithium secondary battery in which the content of the metal oxide excluding lithium in the lithium-metal oxide is 0.1 to 10 parts by weight based on 100 parts by weight of the giant primary particles.

[0021] Another aspect of the present invention provides a method for manufacturing a positive electrode active material for a lithium secondary battery according to the following embodiments.

[0022] The seventh embodiment is, (S1) Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and secondary particles having an average particle size (D50) of 1 to 10 μm formed by aggregating two or more giant primary particles having an average particle size (D50) of 0.5 to 3 μm are prepared, (S2) Mixing and firing one or more metal oxides selected from the group consisting of manganese, nickel, vanadium, and cobalt with the secondary particles to form a lithium-metal oxide coating layer on the surface of the secondary particles by reaction of lithium impurities contained on the surface of the secondary particles with the metal oxide, Relates to a method for manufacturing a positive electrode active material for a lithium secondary battery that does not include a water washing step between the steps (S1) and (S2).

[0023] The eighth embodiment is in the seventh embodiment, The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery, wherein the metal oxide is at least one selected from the group consisting of Mn3O4, Mn2O3, MnO2, NiO, NiO2, V2O5, VO2, Co2O3 and Co3O4.

[0024] The ninth embodiment is any one of the seventh and eighth embodiments, The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery, wherein the metal oxide is at least one selected from the group consisting of Mn3O4 and Co3O4.

[0025] The tenth embodiment is any one of the seventh to ninth embodiments, The present invention relates to a method for preparing a positive electrode active material for a lithium secondary battery, wherein the amount of the metal oxide mixed in step (S2) is 0.1 to 10 parts by weight based on 100 parts by weight of the giant primary particles.

[0026] An eleventh embodiment provides a positive electrode for a lithium secondary battery, comprising the above-mentioned positive electrode active material.

[0027] A twelfth embodiment provides a lithium secondary battery including the above-mentioned positive electrode. Effect of the Invention

[0028] According to one aspect of the present invention, a lithium secondary battery including a nickel-based lithium transition metal oxide positive electrode active material having a secondary particle form in which large primary particles are aggregated has low resistance during charging and discharging, thereby improving output characteristics.

[0029] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0030] [Figure 1] 1 is a SEM image of positive electrode active material particles according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Hereinafter, the embodiment of the present invention will be described in detail. Prior to this, the terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as being in accordance with the meaning and concept of the technical idea of ​​the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the configurations shown in the embodiments described in this specification are merely the most preferred embodiment of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can be substituted for them at the time of this application.

[0032] Throughout this specification, when a part "comprises" another component, it means that the part may further include the other component, not excluding the other component, unless otherwise specified.

[0033] In the present specification and claims, "comprising a large number of crystal grains" means a crystal consisting of two or more crystal grains having an average crystal size in a specific range. In this case, the crystal size of the crystal grains can be quantitatively analyzed using X-ray diffraction analysis (XRD) using CuKα X-rays (Xrα). Specifically, the average crystal size of the crystal grains can be quantitatively analyzed by placing the produced particles in a holder and analyzing the diffraction pattern produced by irradiating the particles with X-rays.

[0034] In the present specification and claims, D50 may be defined as a particle diameter at 50% of the particle size distribution, and may be measured using a laser diffraction method. For example, the average particle diameter (D50) of the positive electrode active material may be measured by dispersing the particles of the positive electrode active material in a dispersion medium, introducing the particles into a commercially available laser diffraction particle size measuring device (e.g., MT3000 manufactured by Microtrac), irradiating the particles with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle diameter (D50) corresponding to 50% of the cumulative volume in the measuring device.

[0035] In the present invention, the term "primary particles" refers to particles that have no apparent grain boundaries when observed at a magnification of 5,000 to 20,000 using a scanning electron microscope.

[0036] In the present invention, the "secondary particles" refer to particles formed by agglomeration of the primary particles.

[0037] In the present invention, the term "single particle" refers to a particle that exists independently of the secondary particles and has no apparent grain boundaries, for example, a particle having a particle size of 0.5 μm or more.

[0038] In the present invention, the term "particle" may mean any one or all of a single particle, a secondary particle, and a primary particle.

[0039] According to one aspect of the present invention, secondary particles having an average particle size (D50) of 1 to 10 μm formed by agglomeration of two or more giant primary particles having an average particle size (D50) of 0.5 to 3 μm; A coating layer of lithium-metal oxide formed on the surface of the secondary particles, The large primary particles are Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ(1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and the metal of the lithium-metal oxide is one or more metals selected from the group consisting of manganese, nickel, vanadium, and cobalt, provide a positive electrode active material for a lithium secondary battery having a lithium impurity content of 0.25% by weight or less.

[0040] <Giant primary particles> Generally, nickel-based lithium transition metal oxides are secondary particles. Such secondary particles can be in a form in which primary particles are aggregated.

[0041] Specifically, when dense nickel-based transition metal hydroxide secondary particles produced by a coprecipitation method are used as a precursor, and the precursor is mixed with a lithium precursor and fired at a temperature below 960 °C, nickel-based lithium transition metal oxide secondary particles in which fine primary particles are aggregated can be obtained.

[0042] However, when a positive electrode active material containing such conventional secondary particles is coated on a current collector and then rolled, the particles themselves crack and the specific surface area increases. If the specific surface area increases, there is a problem that a rock salt-type structure is formed on the surface and the resistance increases.

[0043] In an attempt to solve such problems, a positive electrode active material composed of single particles has been developed. Specifically, unlike the conventional method using dense nickel-based lithium transition metal hydroxide secondary particles as a precursor, by using a precursor that is porous compared to the conventional precursor, it is possible to synthesize at a lower firing temperature for the same nickel content, and a nickel-based lithium transition metal oxide that does not have a further secondary particle form and is single-particleized can be obtained. However, when a positive electrode active material containing such single particles is coated on a current collector and then rolled, although the single particles themselves do not crack, there are problems such as other active materials cracking.

[0044] One aspect of the present invention is to solve such problems.

[0045] When a high-density precursor is fired at a high firing temperature as in the past, it is inevitable that not only the average particle size (D50) of the primary particles but also the average particle size (D50) of the secondary particles will increase.

[0046] Meanwhile, the secondary particles according to one embodiment of the present invention are different from the conventional single particle obtaining method in the following points.

[0047] As described above, conventional single particles are formed by simply increasing the primary firing temperature using a conventional precursor for secondary particles. On the other hand, secondary particles according to one embodiment of the present invention use a separate precursor with high porosity. As a result, large primary particles with large diameters can be grown without increasing the firing temperature, while secondary particles grow relatively insufficiently compared to conventional methods.

[0048] As a result, the secondary particles according to one embodiment of the present invention have the same or similar average particle size (D50) as conventional ones, but have a large average particle size (D50) of primary particles. That is, unlike the general form of conventional positive electrode active materials, that is, a form in which primary particles with small average particle size are aggregated to form secondary particles, the secondary particles according to one embodiment of the present invention provide a form in which large primary particles are aggregated within a certain number of primary particles.

[0049] The large primary particles are those in which the average particle size and average crystal size of the primary particles have grown simultaneously, as compared with the micro primary particles that constitute conventional secondary particles.

[0050] From the perspective of cracks, it is advantageous to have a large average particle size while not having grain boundaries as in conventional single particles. If only the average particle size (D50) of the primary particles is increased by over-firing, a rock salt structure forms on the surface of the primary particles, causing high initial resistance. If the crystal size of the primary particles is also increased, the resistance can be reduced.

[0051] Therefore, the giant primary particles in the present invention are particles that have a large average crystal size as well as a large average particle diameter, and have no apparent grain boundaries.

[0052] When the average particle size and average crystal size of the primary particles grow simultaneously in this manner, the resistance is lowered and it has the advantage of a longer life, compared to conventional single particles, which have a large increase in resistance due to a rock salt structure formed on the surface when fired at high temperatures.

[0053] Thus, compared to conventional single particles, the "secondary particles composed of aggregates of giant primary particles" used in one embodiment of the present invention are advantageous in that resistance is reduced due to an increase in the size of the primary particles themselves and a decrease in the rock salt structure.

[0054] In this case, the average crystal size of the giant primary particles can be quantitatively analyzed by X-ray diffraction analysis (XRD) using CuKα X-rays. Specifically, the produced particles are placed in a holder, and the particles are irradiated with X-rays to generate a diffraction pattern, which can be analyzed to quantitatively analyze the average crystal size of the giant primary particles.

[0055] The average crystal size of the large primary particles may be 200 nm or more, specifically 250 nm or more, and more specifically 300 nm or more.

[0056] In a specific embodiment of the present invention, the average particle size (D50) of the large primary particles constituting the secondary particles is 0.5 to 3 μm. If the average particle size (D50) of the large primary particles is less than 0.5 μm, there is a problem that the reactive specific surface area of ​​the particles increases and degradation is accelerated, and if it exceeds 3 μm, there is a problem that the resistance increases excessively. In view of this, the average particle size (D50) of the large primary particles may be 0.5 to 2 μm, more specifically, 0.8 to 1.5 μm.

[0057] The large primary particles are nickel-based lithium transition metal oxides with a high content of Li a Ni 1-b-c-d Co bMn c Q d O 2+δ (1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, and Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr). In the above formula, a, b, c, d, and δ represent the molar ratios of the respective elements in the nickel-based lithium transition metal oxide).

[0058] At this time, the metal Q doped in the crystal lattice of the primary particles may be located only on a part of the surface of the particles according to the site preference of the element Q, may be located while having a concentration gradient that decreases from the surface of the particles toward the particle center, or may be uniformly present throughout the particles).

[0059] <Secondary particle> The secondary particles according to one aspect of the present invention mean aggregate particles formed by aggregating two or more giant (macro) primary particles. More specifically, it can be an aggregate of about 2 to 30 giant primary particles. The average particle size (D50) of the secondary particles is 1 to 10 μm. If the average particle size (D50) of the secondary particles is less than 1 μm, there is a problem that the reaction specific surface area increases and degradation accelerates, and if it exceeds 10 μm, there is a problem that the resistance excessively increases. From such a point, the average particle size (D50) of the secondary particles can be 2 to 8 μm, more specifically 3 to 6 μm).

[0060] <Coating layer> A lithium-metal oxide coating layer is formed on the surface of the secondary particles. Here, the coating layer can be formed on a part or all of the surface of the secondary particles and can also be located in the gaps between the primary particles. Therefore, the coating layer in the present invention must be interpreted in the sense of including all such properties).

[0061] The metal of the lithium-metal oxide is one or more metals selected from the group consisting of manganese, nickel, vanadium, and cobalt, and may particularly be one or more selected from the group consisting of manganese and cobalt. The lithium-metal oxide is formed by the reaction of a metal oxide with lithium impurities remaining on the surface of the secondary particles, as described later. Such a coating layer can be formed in a stable spinel phase. Thereby, even if the secondary particles are not treated through a water washing process, the lithium impurities remaining on the surface thereof are changed into lithium-metal oxide, so that the content of lithium impurities is reduced to, for example, 0.25% by weight or less, and the phenomenon of output decrease is improved.

[0062] As described above, even if the secondary particles are not treated in a water washing process, the lithium impurities remaining on the surface thereof react with the metal oxide and are changed into lithium-metal oxide, so that the content of lithium impurities contained in the positive electrode active material is reduced to 0.25% by weight or less, thereby improving the phenomenon of output decrease.

[0063] From such a point, the content of the metal oxide excluding lithium in the lithium-metal oxide may be 0.1 to 10 parts by weight based on 100 parts by weight of the primary particles.

[0064] <Method for manufacturing positive electrode active material> The positive electrode active material according to one aspect of the present invention can be manufactured by the following method, but is not limited thereto.

[0065] First, Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and secondary particles having an average particle size (D50) of 1 to 10 μm formed by aggregating two or more giant primary particles having an average particle size (D50) of 0.5 to 3 μm are prepared (step S1).

[0066] Step S1 basically includes a step of mixing a nickel-based transition metal oxide precursor and a lithium precursor and calcining the mixture at a certain temperature or higher, and producing at least one secondary particle including an aggregate of two or more giant primary particles through secondary calcination.

[0067] The method for producing the secondary particles will be further described step by step.

[0068] First, a positive electrode active material precursor containing nickel (Ni), cobalt (Co) and manganese (Mn) is prepared.

[0069] In this case, the precursor for producing the positive electrode active material may be a commercially available positive electrode active material precursor, or may be produced by a method for producing a positive electrode active material precursor known in the art.

[0070] For example, the precursor may be prepared by adding an ammonium cation-containing chelating agent and a basic compound to a transition metal solution containing a nickel-containing source material, a cobalt-containing source material, and a manganese-containing source material, and then subjecting the mixture to a coprecipitation reaction.

[0071] The nickel-containing source material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salts, nickel halides, or combinations thereof.

[0072] The cobalt-containing source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and may be, but is not limited to, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof.

[0073] The manganese-containing source material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, specifically, manganese oxide such as Mn2O3, MnO2, Mn3O4, etc.; manganese salt such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid salt; manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.

[0074] The transition metal solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water, or may be prepared by mixing an aqueous solution of the nickel-containing raw material, an aqueous solution of the cobalt-containing raw material, and the manganese-containing raw material.

[0075] The ammonium cation-containing chelating agent may be, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3, or a combination thereof, but is not limited thereto. Meanwhile, the ammonium cation-containing chelating agent may be used in the form of an aqueous solution, and the solvent used in this case may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.

[0076] The basic compound may be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH)2, a hydrate thereof, or a combination thereof. The basic compound may also be used in the form of an aqueous solution, and the solvent used in this case may be water or a mixture of water and an organic solvent (specifically, an alcohol, etc.) that is uniformly miscible with water.

[0077] The basic compound is added to adjust the pH of the reaction solution, and may be added in an amount such that the pH of the metal solution becomes 9 to 11.

[0078] Meanwhile, the coprecipitation reaction may be carried out in an inert atmosphere such as nitrogen or argon at a temperature of 40°C to 70°C.

[0079] Through the above process, nickel-cobalt-manganese hydroxide particles are produced and precipitated in the reaction solution. By adjusting the concentrations of the nickel-containing raw material, the cobalt-containing raw material, and the manganese-containing raw material, a precursor having a nickel (Ni) content of 60 mol% or more in the total metal content can be produced. The precipitated nickel-cobalt-manganese hydroxide particles can be separated and dried by a conventional method to obtain a nickel-cobalt-manganese precursor. The precursor can be secondary particles formed by agglomeration of primary particles.

[0080] Thereafter, the precursor and the lithium source material are mixed and fired.

[0081] The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it is soluble in water. Specifically, the lithium source material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more of these may be used.

[0082] In the case of a high-nickel (high-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 80 mol % or more, the firing may be performed at 700° C. to 1,000° C., more preferably 780° C. to 980° C., and even more preferably 780° C. to 900° C. The primary firing may be performed in an air or oxygen atmosphere for 10 hours to 35 hours.

[0083] After the firing, a secondary firing may be optionally carried out.

[0084] In the case of a high-nickel (high-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 60 mol % or more, particularly 80 mol % or more, the secondary firing may be performed at 650° C. to 800° C., more preferably 700° C. to 800° C., and even more preferably 700° C. to 750° C. The secondary firing may be performed in an air or oxygen atmosphere, and cobalt oxide or cobalt hydroxide may be added at 20,000 ppm during the secondary firing.

[0085] By controlling the size of the giant primary particles, the molar ratio of lithium to the transition metal, and the sintering temperature through this aggregation process, a positive electrode active material composed of secondary particles having a predetermined average particle size range, which are formed by agglomerating giant primary particles having a predetermined average particle size range, can be manufactured.

[0086] Then, the secondary particles are mixed with an oxide of at least one metal selected from the group consisting of manganese, nickel, vanadium, and cobalt, and sintered to form a lithium-metal oxide coating layer on the surface of the secondary particles by the reaction of the lithium impurities contained on the surface of the secondary particles with the metal oxide (step S2). Here, the secondary particles used in step S2 do not include a water washing step. That is, no water washing step is included between steps (S1) and (S2).

[0087] The metal oxide to be mixed with the secondary particles may be at least one selected from the group consisting of Mn3O4, Mn2O3, MnO2, NiO, NiO2, V2O5, VO2, Co2O3, and Co3O4. In particular, it may be at least one selected from the group consisting of Mn3O4 and Co3O4.

[0088] When such a metal oxide is mixed in an amount that matches the equivalent ratio of the lithium impurities remaining on the surfaces of the secondary particles, and then fired at a temperature of, for example, 350 to 700°C for 2 to 10 hours, the lithium impurities remaining on the surfaces of the secondary particles react with the metal oxide to form a lithium-metal oxide coating layer on the surfaces of the secondary particles.

[0089] The amount of the metal oxide mixed in step (S2) may be 0.1 to 10 parts by weight, more specifically, 0.5 to 10 parts by weight, based on 100 parts by weight of the primary particles.

[0090] <Positive electrodes and lithium secondary batteries> According to yet another aspect of the present invention, there is provided a positive electrode for a lithium secondary battery and a lithium secondary battery, each of which includes the positive electrode active material.

[0091] Specifically, the positive electrode includes a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the above-mentioned positive electrode active material of the present invention.

[0092] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0093] The positive electrode active material layer may further include a positive electrode active material formed of large single particles or secondary particles formed by agglomeration of conventional fine primary particles in addition to the above-mentioned positive electrode active material, and may further include a conductive material and a binder.

[0094] In this case, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may usually be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0095] In addition, the binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0096] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material described above. Specifically, the positive electrode may be manufactured by coating a composition for forming a positive electrode active material layer, which includes the positive electrode active material and, optionally, a binder and a conductive material, on a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0097] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, taking into consideration the coating thickness of the slurry and the manufacturing yield, and to provide a viscosity that allows excellent thickness uniformity to be achieved when the slurry is applied to manufacture a positive electrode.

[0098] Alternatively, the positive electrode may be manufactured by casting the composition for forming a positive electrode active material layer on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0099] According to yet another aspect of the present invention, there is provided an electrochemical device including the positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0100] The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0101] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0102] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to increase the adhesive strength of the negative electrode active material, as in the case of the positive electrode current collector. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0103] The negative electrode active material layer may include a negative electrode active material and, optionally, a binder and a conductive material, and may be manufactured, for example, by coating a negative electrode forming composition including a negative electrode active material and, optionally, a binder and a conductive material on a negative electrode current collector and drying the composition, or by casting the negative electrode forming composition on a separate support and then peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0104] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon may be used as the carbonaceous material. Representative low-crystalline carbons include soft carbon and hard carbon, and representative high-crystalline carbons include amorphous, plate-like, scaly, spherical, or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal-based coke.

[0105] Additionally, the binder and conductive material are the same as those described above for the positive electrode.

[0106] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte impregnation ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0107] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0108] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0109] The organic solvent may be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move.Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), or propylene carbonate (PC); an alcohol solvent such as ethyl alcohol or isopropyl alcohol; a nitrile such as R-CN (R is a hydrocarbon group having a linear, branched, or cyclic structure of C2 to C20, and may contain a double bond aromatic ring or an ether bond); an amide such as dimethylformamide; a dioxolane such as 1,3-dioxolane; or a sulfolane. Among them, carbonate-based solvents are preferable, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant capable of improving the charge / discharge performance of a battery and a low-viscosity linear carbonate-based compound (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) is more preferable. In this case, it is preferable to mix the cyclic carbonate and the linear carbonate in a volume ratio of about 1:1 to about 1:9 for excellent electrolyte performance.

[0110] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt may be within a range of 0.1 to 2.0M. If the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore exhibits excellent electrolyte performance and allows lithium ions to move effectively.

[0111] In addition to the electrolyte components described above, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving battery life characteristics, suppressing a decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.

[0112] A lithium secondary battery containing the positive electrode active material according to the present invention is useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs).

[0113] According to yet another aspect of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0114] The battery module or battery pack may be used as a power source for one or more medium to large devices including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or power storage systems.

[0115] The present invention will now be described in detail with reference to exemplary embodiments so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments described below.

[0116] <Example 1> (Secondary particle production) After 4 liters of distilled water was added to a coprecipitation reactor (volume 20 L), 100 mL of 28 wt% aqueous ammonia solution was added while maintaining the temperature at 50°C. Then, a 3.2 mol / L transition metal solution, which was a mixture of NiSO4, CoSO4, and MnSO4 with a nickel:cobalt:manganese molar ratio of 0.80:0.1:0.1, was continuously added to the reactor at 300 mL / hr through a feeder, and a 28 wt% aqueous ammonia solution was continuously added to the reactor at 42 mL / hr through a separate feeder. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added through a separate feeder to maintain the pH at 9. The mixture was coprecipitation reacted for 10 hours to form precursor particles.

[0117] Ni synthesized through coprecipitation reaction 0.8 Co 0.1 Mn 0.1 The (OH)2 positive electrode active material precursor and the lithium source material LiOH were mixed so that the final Li / Me(Ni,Co,Mn) molar ratio was 1.05, and the mixture was fired at 800°C for 10 hours in an oxygen atmosphere to produce LiNi 0.8 Co 0.1 Mn 0.1 A positive electrode active material represented by O2 was prepared.

[0118] (Formation of coating layer) The secondary particles obtained by the above method and Mn3O4 as a metal oxide, which is a coating source, were mixed in an equivalent ratio of 1 part by weight to 100 parts by weight of the secondary particles, and then fired at 500°C for 5 hours to form a coating layer.

[0119] <Example 2> The same procedure as in Example 1 was carried out, except that the content of the coating source was changed to the content in Table 1 below.

[0120] <Example 3> The same procedure as in Example 1 was carried out, except that the type and content of the coating source were changed to the metal oxide and content in Table 1 below.

[0121] <Example 4> The same procedure as in Example 1 was carried out, except that the type and content of the coating source were changed to the metal oxide and content in Table 1 below.

[0122] <Comparative Example 1> The same procedure as in Example 1 was carried out, except that no coating layer was formed.

[0123] <Comparative Example 2> The same procedure as in Example 1 was carried out, except that no coating layer was formed and the produced secondary particles were washed with water.

[0124] <Comparative Example 3> The same procedure as in Example 1 was carried out, except that the prepared positive electrode active material was washed with water and then a coating layer was formed.

[0125] <Comparative Example 4> The same procedure as in Example 1 was repeated, except that the type and content of the coating source were changed to the metal oxide and content in Table 1 below, and the prepared positive active material was washed with water and then a coating layer was formed.

[0126] <Comparative Example 5> After 4 liters of distilled water was added to a coprecipitation reactor (volume 20 L), 100 mL of 28 wt% aqueous ammonia solution was added while maintaining the temperature at 50°C. Then, a 3.2 mol / L transition metal solution, which was a mixture of NiSO4, CoSO4, and MnSO4 such that the molar ratio of nickel:cobalt:manganese was 0.80:0.1:0.1, was continuously added to the reactor at 300 mL / hr through a feeder, and a 28 wt% aqueous ammonia solution was continuously added to the reactor at 42 mL / hr through a separate feeder. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added through a separate feeder to maintain the pH at 9. The mixture was co-precipitated for 10 hours to form precursor particles. The precursor particles were separated, washed, and then dried in an oven at 130°C.

[0127] Ni synthesized through coprecipitation reaction 0.8 Co 0.1 Mn 0.1 (OH)2) The positive electrode active material precursor and the lithium source material LiOH were mixed so that the final Li / Me(Ni,Co,Mn) molar ratio was 1.05, and the mixture was fired at 700°C for 10 hours in an oxygen atmosphere to produce LiNi 0.8 Co 0.1 Mn 0.1 A positive electrode active material represented by O2 was prepared.

[0128] A coating layer was formed on the secondary particles prepared by the above method in the same manner as in Example 1, except that the coating source shown in Table 1 was used.

[0129] [Experimental Example 1: Observation of Positive Electrode Active Material] A photograph of the positive electrode active material of Example 1 observed under an enlarged scanning electron microscope (SEM) is shown in FIG.

[0130] [Experimental Example 2: Average particle size] D50 is defined as the particle size at 50% of the particle size distribution and was measured using a laser diffraction method.

[0131] [Experimental Example 3: Crystal size of primary particles] The samples were measured using a Bruker Endeavor (CuKα, λ = 1.54 Å) equipped with a LynxEye XE-T position sensitive detector at FDS 0.5°, over the 2θ range of 15° to 90° with a step size of 0.02° and a total scan time of 20 min.

[0132] The measured data were subjected to Rietveld refinement, taking into account the charge (+3 for metals at transition metal sites, +2 for Ni at Li sites) and cation mixing from each site. For crystal size analysis, instrumental broadening was considered using the Fundamental Parameter Approach (FPA) implemented in the TOPAS program made by Bruker, and the entire peak in the measurement range was used for fitting. Peak morphology was fitted using only the Lorenzian contribution in the First Principle (FP) of the peak types available in TOPAS, and strain was not considered at this time.

[0133] [Experimental Example 4. Measurement of lithium impurity content] In order to measure the amount of Li impurities present in the positive electrode active materials obtained in the examples and comparative examples, pH titration was performed. A Metrohm pH meter was used to titrate 1 mL at a time and record the pH. Specifically, the content of lithium by-products on the surface of the positive electrode active material was measured by titrating the pH with 0.1N HCl using a Metrohm pH meter.

[0134] [Experimental Example 5. Resistance characteristics at SOC5] Positive electrodes were manufactured using the positive electrode active materials according to the examples and comparative examples, and the capacity retention rate was measured as follows: A negative electrode active material was a mixture of artificial graphite and natural graphite mixed in a ratio of 5:5, a conductive material was Super P, and a binder was mixed in a weight ratio of 96:1:3 to manufacture a negative electrode slurry, which was then applied to one side of a copper current collector, dried at 130°C, and rolled to a porosity of 30% to manufacture a negative electrode.

[0135] A porous polyethylene separator was interposed between the positive and negative electrodes prepared as above to prepare an electrode assembly. The electrode assembly was then placed inside a case, and an electrolyte was then injected into the case to prepare a lithium secondary battery.

[0136] The electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.0 M in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (EC / EMC / DEC mixed volume ratio = 3 / 4 / 3).

[0137] The manufactured lithium secondary battery full cell was charged at 25°C in CC (constant current)-CV (constant voltage) mode at 1 / 3C to 4.2V, and discharged at a constant current of 1 / 3C to 3.0V. SOC5 was set based on the capacity, and the battery was discharged at a constant current of 2.5C in the SOC5 state for 10 seconds, and the resistance was measured.

[0138] The characteristics and resistance characteristics of the positive electrode active materials according to the examples and comparative examples are shown in Table 1 below.

[0139] [Table 1]

[0140] Referring to the results in Table 1, the positive electrode active material of Comparative Example 1, which did not have a coating layer, had a high lithium impurity content, and the positive electrode active material of Comparative Example 2, which did not have a coating layer and was washed with water, had a reduced lithium impurity content but an increased resistance due to the washing process. Comparative Examples 3 and 4, in which the coating layer was formed after washing the secondary particles with water, had an increased lithium impurity content during the firing process for forming the coating layer. Meanwhile, the positive electrode active material of Comparative Example 5, which used secondary particles made of aggregates of fine primary particles, had a lithium impurity content above a certain level even after the coating layer was formed due to an increased specific surface area.

Claims

1. secondary particles having an average particle size (D50) of 1 to 10 μm formed by agglomeration of two or more giant primary particles having an average particle size (D50) of 0.5 to 3 μm; a coating layer of lithium-metal oxide formed on the surface of the secondary particles; The large primary particles are Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0≦a≦1.5, 0<b<0.2, 0<c<0.2, 0≦d≦0.1, 0<b+c+d≦0.2, −0.1≦δ≦1.0, and Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), The metal of the lithium-metal oxide is at least one metal selected from the group consisting of manganese, nickel, vanadium, and cobalt; The content of lithium impurities in the positive electrode active material is 0.25% by weight or less; The average crystal size of the giant primary particles is 200 nm or more.

2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the metal of the lithium-metal oxide is at least one selected from the group consisting of manganese and cobalt.

3. 3. The positive electrode active material for lithium secondary batteries according to claim 1, wherein the average particle size (D50) of the large primary particles is 0.5 to 2 μm.

4. The positive electrode active material for a lithium secondary battery according to any one of claims 1 to 3, wherein the average particle size (D50) of the secondary particles is 2 to 8 µm.

5. 5. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the content of the metal oxide excluding lithium in the lithium-metal oxide is 0.1 to 10 parts by weight based on 100 parts by weight of the giant primary particles.

6. A method for producing a positive electrode active material for a lithium secondary battery, comprising: (S1) Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0≦a≦1.5, 0<b<0.2, 0<c<0.2, 0≦d≦0.1, 0<b+c+d≦0.2, -0.1≦δ≦1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti and Zr) and having an average particle size (D50) of 0.5 to 3 μm. The secondary particles are formed by agglomerating two or more of the primary particles, and have an average particle size (D50) of 1 to 10 μm. (S2) mixing the secondary particles with an oxide of at least one metal selected from the group consisting of manganese, nickel, vanadium, and cobalt, and firing the mixture to form a lithium-metal oxide coating layer on the surface of the secondary particles, the lithium impurities contained on the surface of the secondary particles reacting with the metal oxide; No water washing step is included between steps (S1) and (S2), A method for producing a positive electrode active material for a lithium secondary battery, the method comprising the steps of: providing a positive electrode active material having a lithium impurity content of 0.25% by weight or less;

7. The metal oxide is Mn 3 O 4 , Mn 2 O 3 , MnO 2 , NiO, NiO 2 , V 2 O 5 , V.O. 2 , Co 2 O 3 and Co 3 O 4 The method for producing a positive electrode active material for a lithium secondary battery according to claim 6, wherein the positive electrode active material is one or more selected from the group consisting of:

8. The metal oxide is Mn 3 O 4 and Co 3 O 4 The method for producing a positive electrode active material for a lithium secondary battery according to claim 6 or 7, wherein the positive electrode active material is one or more selected from the group consisting of:

9. 9. The method of claim 6, wherein the amount of the metal oxide mixed in step (S2) is 0.1 to 10 parts by weight based on 100 parts by weight of the giant primary particles.

10. A positive electrode for a lithium secondary battery comprising the positive electrode active material for a lithium secondary battery according to claim 1 .

11. A lithium secondary battery comprising the positive electrode according to claim 10.

Citation Information

Patent Citations

  • Composite cathode active material, method of preparing the same, and cathode and lithium battery including the composite cathode active material

    JP2019046795A